2021
DOI: 10.1002/pbc.29497
|View full text |Cite
|
Sign up to set email alerts
|

Provider and staff crisis well‐being associated with trust in leadership and baseline burnout

Abstract: Background The impact of the coronavirus 2019 (COVID‐19) pandemic on the emotional health of health care workers continues to be an area of active research. However, few studies have focused on those working in pediatrics and its subspecialties, as well as ancillary and non‐patient‐facing staff. The purpose of this study was to determine the prevalence and associated predictors of burnout and emotional well‐being of providers and staff. Methods An anonymous electronic survey was developed evaluating demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…This thematic finding is consistent with the limited research to date on the impact of the pandemic on pediatric clinicians. Kase et al (2022) described similar feelings of isolation, fear for family members, and compassion fatigue among pediatric physicians, while Moerdler et al (2022) also studied pediatric physicians and described their decreased trust in leadership and high levels of burnout. Silistre et al (2022) studied workers from intensive care units for prevalence of depression and anxiety related to COVid-19 and found one third of study participants had moderate to severe levels of concern and nurses were more likely than other professionals to experience symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This thematic finding is consistent with the limited research to date on the impact of the pandemic on pediatric clinicians. Kase et al (2022) described similar feelings of isolation, fear for family members, and compassion fatigue among pediatric physicians, while Moerdler et al (2022) also studied pediatric physicians and described their decreased trust in leadership and high levels of burnout. Silistre et al (2022) studied workers from intensive care units for prevalence of depression and anxiety related to COVid-19 and found one third of study participants had moderate to severe levels of concern and nurses were more likely than other professionals to experience symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Presentation of COVid-19 in children was relatively mild during the initial wave of the pandemic in 2020 ( American Journal of Nursing , 2021 ; Jackson et al, 2022 ; Khan et al, 2022 ; Rubenstein et al, 2021 ) with more severe illness seen in older children, those with higher BMI, and those with underlying conditions ( Elwell et al, 2021 ; Guzman et al, 2022 ; Rubenstein et al, 2021 ). Regardless, pediatric clinicians have reported burnout ( Moerdler et al, 2022 ), fear of exposure, anxiety, and depression ( Silistre et al, 2022 ; Sinsky et al, 2021 ), moral distress ( Elwell et al, 2021 ), a sense of being undervalued by their organization ( Kase et al, 2022 ), and an intent to decrease work hours ( Sinsky et al, 2021 ). One qualitative study of pediatric nurses in a single setting focused on those deployed to care for adults during the early days of the pandemic, and chronicled concerns for safety, feeling unprepared yet committed to persevering together.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that a leader's skills correlate strongly with lower burnout rates and higher job satisfaction rates among their staff. 3,20,21 However, leaders are not all-powerful and are constrained by mandates to meet budgetary, provider productivity, patient access, and medical documentation metrics. Leaders such as division chiefs and department chairs often have limited input into health system decisions such as which electronic health record to choose.…”
Section: Leadership Responsibilitiesmentioning
confidence: 99%
“…The importance of organizational factors emphasizes the critical role that leaders play in driving engagement. Indeed, it has been shown that a leader's skills correlate strongly with lower burnout rates and higher job satisfaction rates among their staff 3,20,21 . However, leaders are not all‐powerful and are constrained by mandates to meet budgetary, provider productivity, patient access, and medical documentation metrics.…”
Section: Importance Of Diversity and Graceful Self‐promotionmentioning
confidence: 99%
See 1 more Smart Citation